Answer:

**Answer:**

$90

**Step-by-step explanation:**

300×0.70=210

300-210=90

What’s the LCD Of 5/8

The volume of an object is given as a function of time by V = A + B t + C t4 . Find the dimension of the constant C

Question 8 of 10If f(x) = 5x – 2 and g(x) = 2x + 1, find (f+g)(x).O A. 4x-3O B. 3x - 1C. 7x-1O D. 7x-3SUBM

Question 5What is the measure of the missing angle? Triangle with two of its angles measuring 125 degrees and 42 degrees. 42° 125° 13° 3°

1) Which number line belowshows x 4?a)1 2 3 4 5 6b)0 1 2 3 4 5 6C)26O i 2 3 4D)50 1 23 4 56ABооооСD

The volume of an object is given as a function of time by V = A + B t + C t4 . Find the dimension of the constant C

Question 8 of 10If f(x) = 5x – 2 and g(x) = 2x + 1, find (f+g)(x).O A. 4x-3O B. 3x - 1C. 7x-1O D. 7x-3SUBM

Question 5What is the measure of the missing angle? Triangle with two of its angles measuring 125 degrees and 42 degrees. 42° 125° 13° 3°

1) Which number line belowshows x 4?a)1 2 3 4 5 6b)0 1 2 3 4 5 6C)26O i 2 3 4D)50 1 23 4 56ABооооСD

Answer:x = negative 4

Step-by-step explanation:

The given equation is expressed as

1/4 × x - 1/8 = 7/8 + 1/2 × x

x/4 - 1/8 = 7/8 + x/2

First step is to find the lowest common multiple of the left hand side of the equation and the right hand side of the equation. Then, we would multiply both sides of the equation by the lowest common multiple. The lowest common multiple is 8. Therefore

x/4 × 8 - 1/8 × 8 = 7/8 × 8 + x/2 × 8

2x - 1 = 7 + 4x

7 + 4x = 2x - 1

Subtracting 2x and 7 from the left hand side of the equation and the right hand side of the equation, it becomes

7 - 7 + 4x - 2x = 2x - 2x - 1 - 7

2x = - 8

x = - 8/2 = - 4

**Answer:**

**Step-by-step explanation:**

-4

**Answer:**

3/2 inches

**Step-by-step explanation:**

**Answer:**

The sweater was 30% off

**Step-by-step explanation:**

To find this answer you need to simply dived 15 ÷ 50 to get the answer of 0.3 and 0.3 as a percent would be 30 making the sweater 30% off

The answer is 38 peas per pod

228÷6 = 38

Glad to help you :)

228÷6 = 38

Glad to help you :)

By dividing the total number of peas (228) by the number of peas per pod (6), we find that Gregor Mendel has 38 pods of peas.

This question is asking how many **pods** of peas Gregor Mendel has if he has a total of 228 **peas** and each pod contains 6 peas. To find out this, you can divide the total number of peas by the number of peas per pod.

So, 228 peas ÷ 6 peas/pod = **38 pods**.

Therefore, Gregor Mendel has 38 pods of peas that he is examining for his research.

#SPJ2

**Step-by-step explanation:**

Growth in population each year = 3%(1500)

= 3/100 × 1500

= 3 × 15

= 45

Therefore, the growth in population in 6 years

= 6 × 3%(1500)

= 6 × 45

= 270

Hence, the population after 6 years = 1500 + 270

= 1770

**Answer: 7z + 17**

**Step-by-step explanation: add 15 and 2**